ПЕДАГОГИКА ВА ТАЪЛИМ СОҲАСИДАГИ ИСЛОҲОТЛАРГА БИР НАЗАР (1991-2010 йй) - Абдуллаев, Ўктам (INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE on the topic: “Priority areas for ensuring the continuity of fine art education: problems and solutions”, 2023)
Ўзбекистон, таълим, мактаб, педагогика, институт, университет, ўқитувчи, талаба, йўналиш, билим,олий, факультет.